Hodgkin lymphoma involving the tonsil misdiagnosed as tonsillar carcinoma: A case report and review of the literature. Issue 7 (February 2018) - Qin, You; Lu, Lijuan; Lu, Yanwei; Yang, Kunyu
Abstract: Rationale: Primary Hodgkin lymphoma (HL) involving the tonsil is extremely rare. Only about 20 such cases with verification of biopsy and immunohistochemistry have been reported. Because of its rarity and unremarkable clinical presentation, a timely correct diagnosis is very challenging. Patient concerns: A 43-year-old man complained left tonsillar enlargement and painless masses in left neck, with night sweat. The clinical examination found a marked tonsillar asymmetry, with an enlarged left tonsil and ipsilateral cervical lymphadenopathy and a normal right tonsil. Diagnosis: The patient was initially regarded as tonsillar lymphoepithelial carcinoma. Interventions: The patient received a resection of left tonsil and left cervical masses and then was definitively diagnosed as HL (IIEB). He was managed by 6 cycles of chemotherapy (adriamycin, bleomycin, vinblastine, and dacarbazine) and radiotherapy to the Waldeyer ring. Outcomes: The patient has been disease free for more than 3 years after diagnosis. Lessons: As the reason of an extreme rare occurrence of HL involving the tonsil, doctors can easily misdiagnose the disease as tonsillar lymphoepithelial carcinoma. This case serves as a reminder important role of biopsy.